USM VC URGES STUDENTS TO GO FOR APEX SCHOLAR CERTIFICATION - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 30 August 2016 – The ViceChancellor of Universiti Sains Malaysia (USM) Professor Dato' Dr. Omar Osman is urging the newlyenrolled students for the academic session 2016/2017 to seize the opportunity to obtain the newlyintroduced APEX Scholar certificate.